The Factors that may attract Petra Christian University Students as a New Target Market to visit Seventeen Skyview Resto & Lounge of Harris-Pop! Hotels & Conventions on Weekdays - Stefanie Lawrence (Kata Kita: Journal of Language, Literature, and Teaching, 2019)
This project aims to solve the problem regarding the low number of customers coming to Seventeen Skyview Resto & Lounge on weekdays. I intended to conduct an in-depth research, with the objective is to identify the factors that can be used to attract the new target market to come to this restaurant on weekdays. The main tool I used on this research is the questionnaire form, and the main respondents of this research are fifty students from seventeen different majors in Petra Christian University. The final outcome of this project is a research report as the summary of the questionnaire forms that have been filled out by fifty students of Petra Christian University. This research report will be a beneficial tool for the restaurant to understand the perspectives of Petra Christian University students, who can be categorized as the new potential target market for this restaurant to come on weekdays. Keywords: Research, Respondents, Questionnaire Form, Report